2019
DOI: 10.1002/jmrs.330
|View full text |Cite
|
Sign up to set email alerts
|

Short‐duration post CT‐guided thoracic biopsy monitoring‐ clinical experience with 440 patients

Abstract: Purpose With several studies recording a higher percentage of complications in the first hour of post‐biopsy, this study sought to evaluate the safety in the reduction in post‐biopsy patient monitoring time after computed tomography (CT)‐guided thoracic biopsies, providing a basis for further research. Materials and Methods This was a retrospective study involving patients who were referred to our centre for CT‐guided thoracic biopsies from January 2010 to December 2017. Patients who presented with no complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…5 Other similar studies found that a short observational period of 30 min to 4-h post-biopsy is feasible. 6,7 The implication of this could mean greater efficiency with patients leaving the hospital earlier and therefore requiring less funds and time from personnel for post-biopsy assistance. Frimpong et al concluded that observational period postbiopsy as little as 30 min was proven to be sufficient in cases where no imminent post-procedural complications was presented after a routine CT scan following a CT-guided thoracic biopsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5 Other similar studies found that a short observational period of 30 min to 4-h post-biopsy is feasible. 6,7 The implication of this could mean greater efficiency with patients leaving the hospital earlier and therefore requiring less funds and time from personnel for post-biopsy assistance. Frimpong et al concluded that observational period postbiopsy as little as 30 min was proven to be sufficient in cases where no imminent post-procedural complications was presented after a routine CT scan following a CT-guided thoracic biopsy.…”
Section: Discussionmentioning
confidence: 99%
“…Frimpong et al concluded that observational period post-biopsy as little as 30 min was proven to be sufficient in cases where no imminent post-procedural complications was presented after a routine CT scan following a CT-guided thoracic biopsy. 7 Deciding the length of the observational period should not only be decided on the basis of a low complication rate, but also the consequences of the complication. In this study, 23% ( n = 5) out of the 22 patients with complications needed post-procedural therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no current consensus regarding the appropriate period. 2 Some institutions keep patients for post-procedure monitoring for 4 h, but with some others, the observation period can be as short as 30 min. 2,11,12 The primary aim of this study is to determine the timeframe at which pneumothoraces occur following CT-guided lung biopsy to guide an appropriate post-procedure observation time.…”
Section: Introductionmentioning
confidence: 99%
“…Depending on location, the frequency of complications differs, being especially low in musculoskeletal interventions (0.2%) (3). Frequencies are higher in thoracic biopsies with a range of 5.7%–10% (46). The vast majority of complications occur within 4–6 h after biopsy; thus, current guidelines recommend postprocedural observation for 1–6 h, including clinical observation, pain evaluation using standard numeric rating scales, and monitoring of vital signs (1).…”
Section: Introductionmentioning
confidence: 99%